Spondyloepimetaphyseal dysplasia EXTL3‐deficient type: Long‐term follow‐up and review of the literature. Issue 10 (4th June 2021) - Akalın, Akçahan; Taskiran, Ekim Z.; Şimşek‐Kiper, Pelin Özlem; Utine, Eda; Alanay, Yasemin; Özçelik, Uğur; Boduroğlu, Koray
Abstract: Spondyloepimetaphyseal dysplasia (SEMD) is a group of genetic skeletal disorders characterized by disproportionate short stature, and varying degrees of vertebral, epiphyseal, and metaphyseal involvement of the skeleton. According to the Nosology and classification of genetic skeletal disorders 2019 revision, more than 20 types of SEMD have been identified, and SEMD with immune deficiency, EXTL3 type is one of the newcomers. Affected individuals display variable skeletal abnormalities and neurodevelopmental findings. Liver and kidney cysts have also been reported frequently. Patients may exhibit varying degrees of immune deficiency as well. To date, only 14 patients from 9 unrelated families with SEMD with immune deficiency, EXTL3 type have been reported in the literature. We report a new patient who is currently 15 years old in whom cystic liver lesions were detected in the prenatal period. Disproportionate short stature, mild developmental delay and a T − NK + B + immunological profile were detected in the postnatal follow‐up. Exome sequence analysis revealed a previously reported homozygous missense variant in exon 3 c.953C > T; p.(Pro318Leu) in EXTL3 .